Pengaruh Beban Kerja terhadap Kinerja Panitia Pemungutan Suara (PPS) Pemilu 2024 Sekecamatan Bajubang Kabupaten Batang Hari - Darma, Budi; Wulansari, Kasiyati Yunita; Damanik, Eva Setia Rini; Ningsih, Yulia Istia; Fauziah, Fauziah (Universitas Batanghari Jambi, 2024)
This research examines the influence of workload on the performance of the Polling Station Committee (PPS) for the 2024 Election in the Bajubang Subdistrict, Batang Hari Regency. The research sample consists of 30 individuals. The analytical tools used include simple linear regression, t-test, and coefficient of determination. In the t-test results, the workload variable significantly influences the performance of the Polling Station Committee (PPS) for the 2024 Election in the Bajubang Subdistrict, Batang Hari, individually (partial). In the Coefficient of Determination test, the workload variable affects the performance of the Polling Station Committee (PPS) for the 2024 Election in the Bajubang Subdistrict, Batang Hari, by 36.6%. Meanwhile, 63.4% of the performance of the Polling Station Committee (PPS) for the 2024 Election in the Bajubang Subdistrict, Batang Hari, is influenced by other variables not examined in this study.